Phân tích chuỗi giá trị cây sả trên địa bàn huyện Tuy Phước, tỉnh Bình Định - Nguyễn Thị Hạnh; Phạm Diệp Toàn; Nguyễn Thị Huỳnh Nhã (My University, 2021)
Phân tích chuỗi giá trị cây sả trên địa bàn huyện Tuy Phước, tỉnh Bình Định
Keywords: Chuỗi giá trị